Influence of Titanium Oxide and Calcium Carbonate Powder as Additives on Tribological Characteristics of Lubricants - Abhinit Shrivastava; Surinder Kumar; Sumit Kumar; Hemant Kumar; Sumika Chauhan; Govind Vashishtha; Rajesh Kumar (Lubricants)
The properties of lubricating oils are greatly enhanced by the incorporation of additives. With technological advancements, numerous additives have been developed and proven effective for this purpose. Some additives enhance anti-wear and anti-friction characteristics, while others improve the oil’s viscosity index. It has been noted that certain additives influence more than one property of the lubricating oil. In this study, a mixture of TiO2 at 0.2 wt.%, 0.3 wt.%, and 0.4 wt.% and CaCO3 at 0.4 wt.%, 0.6 wt.%, and 0.8 wt.% was used as an additive in gear oil EP140 to prepare the samples. A pin-on-disc test was conducted for the tribological characterization of the various samples. A combination of 0.2 wt.% TiO2 and 0.4 wt.% CaCO3 particles in the gear oil resulted in a remarkable 88.23% reduction in wear compared to the base gear lubricating oil (EP140). The combination of 0.3 wt.% TiO2 and 0.6 wt.% CaCO3 particles in the gear oil led to a significant 36.84% reduction in the coefficient of friction. Field Emission Scanning Electron Microscopy (FESEM) revealed that the pin tested with sample S1 (gear oil containing 0.2 wt.% TiO2 and 0.4 wt.% CaCO3) exhibited a smoother wear surface than the base lubricating oil.